Matematyka
erzetka
1

a) . (x+4) - (3-2x) = (3x+4) - (6+x) b). -(3-x) + (2x+2)=-(1-2x)+(2x-15) Dam naj pierwszej osobie z dobrym rozwiązaniem .

+0
(3) Odpowiedź
Rurku

a) (x+4) - (3-2x) = (3x+4) - (6+x) x+4-3+2x=3x+4-6-x 3x+1=2x-2 x=-3 b)-(3-x) + (2x+2)=-(1-2x)+(2x-15) -3+x+2x+2=-1+2x+2x-15 3x-1=4x-16 x=15

kamil171998

a) . (x+4) - (3-2x) = (3x+4) - (6+x) x+4-3+2x = 3x+4-6-x x+2x -3x+x = 4-6 -4 +3 x=-3 b). -(3-x) + (2x+2)=-(1-2x)+(2x-15) -3+x+2x+2=-1+2x+2x-15 x+2x-2x-2x=-1-15-2+3 -x=-15/:(-1) x=15

Krystus17

a) . (x+4) - (3-2x) = (3x+4) - (6+x) x+4-3+2x=3x+4-6-x x+2x-3x+x=4-6-4+3 x=-3 b). -(3-x) + (2x+2)=-(1-2x)+(2x-15) -3+x+2x+2=-1+2x+2x-15 x+2x-2x-2x=-1-15+3-2 -x=-15/x_1 x=15

Dodaj swoją odpowiedź